The Effectiveness of Digital Game-Based Vocabulary Learning: A Framework-Based View of Meta-Analysis - Chen, Meng-Hua; Tseng, Wen-Ta; Hsiao, Tsung-Yuan (British Journal of Educational Technology, 2018)
This study presents the results of a meta-analytic study about the effects of digital game-based learning (DGBL) on vocabulary. The results of the study showed that the effects of DGBL on vocabulary learning may vary with game design features (Q = 5.857, df = 1, p = 0.016), but not with learners' age (Q = 0.906, df = 1, p = 0.341) or linguistic background (Q = 0.0001, df = 1, p = 0.994). In light of the research findings, Csikszentmihalyi's (1990) Flow Theory was adopted to theorize the role of game design in DGBL. It is proposed that a hierarchy should exist on the "challenge" axis in the Flow Theory, with adventure-oriented games above non-adventure-based games along the "challenge" axis. The theoretical underpinning is that the dynamic equilibrium between challenge and abilities can function independently of the effects of learners' age and linguistic background.
Keywords: Age Differences; Computer Games; Design; Instructional Effectiveness; Meta Analysis; Native Language; Role; Statistical Analysis; Theories; Vocabulary Development